2010
DOI: 10.2337/db09-1336
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 1 Blockade Ameliorates Albuminuria in Experimental Diabetic Nephropathy

Abstract: OBJECTIVECannabinoid receptor 1 (CB1) is localized in the central nervous system and in peripheral tissues involved in energy metabolism control. However, CB1 receptors are also expressed at low level within the glomeruli, and the aim of this study was to investigate their potential relevance in the pathogenesis of proteinuria in experimental type 1 diabetes.RESEARCH DESIGN AND METHODSStreptozotocin-induced diabetic mice were treated with N-(piperidin-1-yl)-5-(4-iodophenyl)-1-(2,3-dichlorophenyl)-4-methyl-1H-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
159
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(174 citation statements)
references
References 39 publications
13
159
2
Order By: Relevance
“…It was shown that XLR-11 and UR-144 had Δ9-THS-like activity in animals and bind to the brain cannabinoid receptor (CB1 receptor) in in vitro studies. CB1 receptors are also expressed in kidney cells, including podocytes and proximal tubule cells (10)(11)(12), and we suggest that the AKI related to SCB might be related to CB1 receptors in the kidneys. Th ere are limited data on the CB1 receptor and kidney function.…”
Section: Synthetic Cannabinoids and Acute Kidney Injurymentioning
confidence: 73%
See 1 more Smart Citation
“…It was shown that XLR-11 and UR-144 had Δ9-THS-like activity in animals and bind to the brain cannabinoid receptor (CB1 receptor) in in vitro studies. CB1 receptors are also expressed in kidney cells, including podocytes and proximal tubule cells (10)(11)(12), and we suggest that the AKI related to SCB might be related to CB1 receptors in the kidneys. Th ere are limited data on the CB1 receptor and kidney function.…”
Section: Synthetic Cannabinoids and Acute Kidney Injurymentioning
confidence: 73%
“…Th ere are limited data on the CB1 receptor and kidney function. However, blockade of CB1 receptors has been shown to have protective eff ects on renal function and ameliorate albuminuria in certain groups of mice (10,11,13).…”
Section: Synthetic Cannabinoids and Acute Kidney Injurymentioning
confidence: 99%
“…Several recent reports (Table 1) have documented the presence of functional CB 1 receptor in the entire kidney [15,[33][34][35][36][37][38][40][41][42], including different parts of the nephron such as afferent and efferent arterioles [39], glomeruli [33,38,40,42,43], tubules [15], the loop of Henle [44], and collecting ducts [15]. It is also expressed in various subtypes of kidney cells such as podocytes [33,41,43,45,46], proximal and distal tubular epithelial cells [15,34,37,38,40,41,[47][48][49], and mesangial cells [50,54]. Moreover, CB 1 receptors are expressed in human clear-and chromophobe-renal cell carcinomas, as well as in renal oncocytoma [55,56].…”
Section: The Renal Ecb Systemmentioning
confidence: 99%
“…In the first model induced by streptozotocin (STZ), kidney expression of the CB 1 receptor is enhanced in both diabetic mice [33] and rats [37]. More specifically, colocalization of the CB 1 receptor with nephrin points to their predominant expression in podocytes.…”
Section: Role Of Cb 1 Receptors In Dnmentioning
confidence: 99%
See 1 more Smart Citation